2018
DOI: 10.1007/s00210-018-1538-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the effects of ochratoxin A and aristolochic acid on the inflammation and oxidative stress in the liver and kidney of weanling piglets

Abstract: Ochratoxin A (OTA) and aristolochic acid (AA) are toxins that can frequently contaminate cereals and cereals-based products. The present study has realized a comparison between the effect of OTA and AA on oxidative stress and inflammation in both the liver and kidney of pigs as major organs involved in the metabolism of xenobiotics. Fifteen pigs (five pigs/group) were randomly distributed in three groups (control, OTA, and AA) and were fed diets contaminated or not with 250 μg toxin/kg for 28 days. Consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Second, in addition to hypoxia, HIF‐1α has been reported to be upregulated by other factors, such as nitric oxide, TNF‐α, angiotensin II, IL‐1, and insulin 39‐41 . Some of these factor(s), such as TNF‐α and IL‐1, have been reported to be increased in AAN 42,43 . These factors may induce the upregulation of HIF‐1α, but the precise mechanism needs to be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in addition to hypoxia, HIF‐1α has been reported to be upregulated by other factors, such as nitric oxide, TNF‐α, angiotensin II, IL‐1, and insulin 39‐41 . Some of these factor(s), such as TNF‐α and IL‐1, have been reported to be increased in AAN 42,43 . These factors may induce the upregulation of HIF‐1α, but the precise mechanism needs to be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Some of these factor(s), such as TNF-α and IL-1, have been reported to be increased in AAN. 42,43 These factors may induce the upregulation of HIF-1α, but the precise mechanism needs to be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although the hepatotoxicity of AA-I has been widely presented in several works, the comprehension of its underlying mechanism remains unknown. It has been indicated that oxidative stress plays an essential role in AA-I-induced liver damage [ 10 , 38 ]. Oxidative stress disrupts the oxidation–reduction balance, which is commonly seen in many biological reactions with increases in ROS levels [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have indicated that AAN is manifested by rapidly progressive interstitial nephropathy [ 7 ], and is thought to occur through multiple mechanisms, such as renal cell apoptosis, renal interstitial inflammatory cell infiltration, oxidative stress and DNA adducts [ 8 , 9 ]. Recently, AA-I-induced DNA adduct accumulation was detected in the liver, which implies that AA-I can induce hepatotoxicity [ 10 , 11 ]. At the same time, many reports have evidenced the direct association between the use of AA and hepatitis-B-related liver cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large number of in vivo and in vitro experiments have found that DON can induce the generation of free radicals in addition to mycotoxins, so some studies have also used DON to induce oxidative stress [15,38]. The results of Marin et al (2018) indicated that ochratoxin A (OTA) and aristolochic acid (AA) could induce inflammation and oxidative stress in the liver and kidney of weanling piglets [39].…”
Section: Model Of Oxidative Stress In Pigsmentioning
confidence: 99%